Is there an institutional structure conducive to judicial independence? An overview of ruling constitutions in Latin America - Magalhães, Rebecca (2014)
What determines the nature of judicial review and the way it operates in the new democracies? Institutional factors seem to impact the independence and power of courts and therefore are often used to explain their behavior. Mechanisms such as composition of the courts, jurisdiction, and selection of members of the term commonly listed in detail in constitutional texts, signaling that the autonomy of the courts is traditionally a desirable ideal for constituents. This article aims to analyze how certain characteristics may be crucial in promoting judicial independence and ultimately determine which are present in the constitutional courts in Latin America.